Long-Term Non-invasive Ventilation in Children: Current Use, Indications, and Contraindications - Praud, Jean-Paul (Frontiers in Pediatrics, 2020)
This review focuses on the delivery of non-invasive ventilation—i.e., intermittent positive-pressure ventilation—in children lasting more than 3 months. Several recent reviews have brought to light a dramatic escalation in the use of long-term non-invasive ventilation in children over the last 30 years. This is due both to the growing number of children receiving care for complex and severe diseases necessitating respiratory support and to the availability of LT-NIV equipment that can be used at home. While significant gaps in availability persist for smaller children and especially infants, home LT-NIV for children with chronic respiratory insufficiency has improved their quality of life and decreased the overall cost of care. While long-term NIV is usually delivered during sleep, it can also be delivered 24 h a day in selected patients. Close collaboration between the hospital complex-care team, the home LT-NIV program, and family caregivers is of the utmost importance for successful home LT-NIV. Long-term NIV is indicated for respiratory disorders responsible for chronic alveolar hypoventilation, with the aim to increase life expectancy and maximize quality of life. LT-NIV is considered for conditions that affect respiratory-muscle performance (alterations in central respiratory drive or neuromuscular function) and/or impose an excessive respiratory load (airway obstruction, lung disease, or chest-wall anomalies). Relative contraindications for LT-NIV include the inability of the local medical infrastructure to support home LT-NIV and poor motivation or inability of the patient/caregivers to cooperate or understand recommendations. Anatomic abnormalities that interfere with interface fitting, inability to protect the lower airways due to excessive airway secretions and/or severely impaired swallowing, or failure of LT-NIV to support respiration can lead to considering invasive ventilation via tracheostomy. Of note, providing home LT-NIV during the COVID 19 pandemic has become more challenging. This is due both to the disruption of medical systems and the fear of contaminating care providers and family with aerosols generated by a patient positive for SARS-CoV-2 during NIV. Delay in initiating LT-NIV, decreased frequency of home visits by the home ventilation program, and decreased availability of polysomnography and oximetry/transcutaneous PCO2 monitoring are observed. Teleconsultations and telemonitoring are being developed to mitigate these challenges.